Clinico-Laboratory Profile and Immediate Outcomes of Hyperbilirubinemic Babies Admitted in Kanti Children Hospital - Nepal, Deepeshwara; Banstola, Dinesh; Khakal, Ajaya Kumar; Mishra, Udbhabhat; Maheseth, Chandeshawar (Journal of Nepal Paediatric Society, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Introduction: Jaundice is an important problem in the neonatal period especially in the first week of life. Our objective of the study is to find out the immediate outcome of hyperbilirubinemic babies admitted in Kanti Children Hospital. Methodology: This is a retrospective study and carried out in tertiary care paediatric hospital. Results: Altogether 73 babies were enrolled in the study. Male babies outnumbered the female (72.6% vs. 27.4%).Only 2.4% babies were near-term. LBW babies constitute 19.2% of the study population.86.3% of babies also have clinical sepses as defined by WHO criteria. Almost half of the babies have mild hyperbilirubinemia (15-19.9 mg/dl). Most of the babies (94.5%) improved and the mortality was 5.5%. Conclusion: Healthy term babies with a serum bilirubin <17mg/dl should not be admitted for routinely as they do not need phototherapy. Phototherapy is effective in most of the time, but exchange transfusion should also be carried out when phototherapy fails. Causes of hyperbilirubinemia should be searched extensively especially to rule out haemolysis. Key words: hyperbilirubinemia, kernicterus, neonates, phototherapy DOI: 10.3126/jnps.v30i1.2457 Journal of Nepal Paediatric Society Vol.30(1) 2010 31-36